Approaches for Health Technology Assessment in Europe: Situational Analysis - Slaveyko Djambazov; Toni Vekov (Journal of Biomedical & Clinical Research)
Health technology assessment (HTA) isaprocess, which should answer the question“Isagiven health technology/medication worth its price for the value it provides?” In the spirit of the amendments to the Bulgarian Health Insurance Act and institutionalization of HTA, our team prepared this situational evaluation aiming to throw light on the practices and approaches to HTAin European countries. As awhole,we can identify two types of agencies that perform it: those servicing the population of an entire nation oraregion, and those working at the level of hospitals oranetwork of hospitals. All the agencies studied have two common characteristics. First, they were created withanon-profit purpose and second, all of them are financed by public funds inavariety of ways. It also becomes clear from the comparative analysis performed that the ways HTAis conducted in Europe differ from country to country. Irrespective of the variations, the common aspiration is that the value forapatient, to which the approved health technologies contribute, should be greater than the price to be paid for them. Bulgaria is may be the last EUstate to implement HTAin its domestic legislation and this also gives the advantage of having and using the experience of the other countries. Establishing an independent structure, which is appointed to prepare local health technologies assessment would result in transparent decision-making, participation of all concerned parties and optimization of the budget for medicines regarding the effectiveness/benefit ratio, as well as expenses.